The incredible shrinking man - Matheson, Richard (Tor, 2004)
Scott Carey is enveloped by a glowing radioactive fog, which causes him to begin shrinking gradually but relentlessly. Eventually, he is only two inches tall and must live in a dollhouse set up in his livingroom. The minor irritations of his abnormal-sized life assume life and death proportions, as he duels with a now monstrous spider, escapes from a clawing house cat, and battles to survive in the over-sized world around him